VE-cadherin cleavage by LasB protease from Pseudomonas aeruginosa facilitates type III secretion system toxicity in endothelial cells. - Guillaume Golovkine; Eric Faudry; Stéphanie Bouillot; Romé Voulhoux; Ina Attrée; Philippe Huber (PLoS Pathogens)
Infection of the vascular system by Pseudomonas aeruginosa (Pa) occurs during bacterial dissemination in the body or in blood-borne infections. Type 3 secretion system (T3SS) toxins from Pa induce a massive retraction when injected into endothelial cells. Here, we addressed the role of type 2 secretion system (T2SS) effectors in this process. Mutants with an inactive T2SS were much less effective than wild-type strains at inducing cell retraction. Furthermore, secretomes from wild-types were sufficient to trigger cell-cell junction opening when applied to cells, while T2SS-inactivated mutants had minimal activity. Intoxication was associated with decreased levels of vascular endothelial (VE)-cadherin, a homophilic adhesive protein located at endothelial cell-cell junctions. During the process, the protein was cleaved in the middle of its extracellular domain (positions 335 and 349). VE-cadherin attrition was T3SS-independent but T2SS-dependent. Interestingly, the epithelial (E)-cadherin was unaffected by T2SS effectors, indicating that this mechanism is specific to endothelial cells. We showed that one of the T2SS effectors, the protease LasB, directly affected VE-cadherin proteolysis, hence promoting cell-cell junction disruption. Furthermore, mouse infection with Pa to induce acute pneumonia lead to significant decreases in lung VE-cadherin levels, whereas the decrease was minimal with T2SS-inactivated or LasB-deleted mutant strains. We conclude that the T2SS plays a pivotal role during Pa infection of the vascular system by breaching the endothelial barrier, and propose a model in which the T2SS and the T3SS cooperate to intoxicate endothelial cells.